The contribution of animal breeding to reducing the environmental impact of livestock production - de Haas, Yvette (Burleigh Dodds Series in Agricultural Science, 2021)
Animal production is responsible for 14.5% of total anthropogenic greenhouse gas (GHG) emissions. Approximately half of these emissions originate directly from animal production, whereas the other half comes from feed production. Animal breeding aims at improving animal production and efficient use of resources, which results in a reduction of environmental impact. In this chapter we quantify the contribution of animal breeding to reducing the environmental impact of the four major livestock species in the Netherlands, namely laying hens, broilers and pigs (all monogastrics), and dairy cattle (ruminants). For eggs, and broiler and pig meat we focussed on GHG emissions and nitrogen and phosphorus efficiency, whereas for dairy we focussed on enteric methane emissions, an important contributor to GHG emissions. Results showed that current selection strategies on increased (feed) efficiency indirectly reduces environmental impact per unit of animal product by about 1% per year. If the aim is to directly select on environmental traits, recording of new traits is required; e.g., nitrogen and phosphorus contents of meat and eggs, and methane emission of individual dairy cows.